PENGARUH SISTEM PENGENDALIAN DIAGNOSTIK DAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN - Nanu Hasanuh (Eqien - Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine how much influence the implementation of diagnostic control system and accounting information system on employees performance at PT. Bravo Satya Kencana Karawang. Research approach is descriptive and verifikatif analysis by using primary data. Sampling technique is nonprobability sampling with purposive sampling method. Statistical analysis in this study is multiple regression analysis test, correlation, hypothesis testing using t test and F test. The population of this study is all employees in the company in PT. Bravo Satya Kencana Karawang, the research sample is 40 people with the source data obtained through the results of filling questionnaires. Based on the results of research conducted can be seen that partially implementation of diagnostic control system affect on employee performance. The influence of the implementation of diagnostic control system 0.257, and accounting information system 0.299 on employee performance. Simultaneously, diagnostic control systems and accounting information system on the employees performance at the level of sig. 0.008.